Motivations and Pathways in Higher Education Language Learning: Evidence to Inform the Next Phase of Languages Connect - Wang, Hongfei; Imperial, Rowland; McNamara Cullen, Erin (Trinity College Dublin, 2026)
This report examines the motivations, participation pathways, and experiences that shape foreign language learning in Irish higher education, providing evidence to inform the next phase of Languages Connect: Ireland's Strategy for Foreign Languages in Education. Commissioned by Post-Primary Languages Ireland (PPLI) on behalf of the Department of Education and Youth, the study employed a mixed-methods design combining survey data from 462 students across Trinity College Dublin and South East Technological University with interviews involving 17 students and seven educators and institutional representatives. The findings demonstrate that students hold consistently positive attitudes towards language learning and recognise its value for communication, intercultural understanding, personal development, international engagement, and future careers. However, continued participation is influenced less by learner motivation than by structural factors, including curriculum flexibility, progression opportunities, and institutional provision. The report recommends strengthening continuity across the language learning continuum, expanding flexible participation pathways, recognising multilingualism as a strategic national resource, and supporting the responsible integration of artificial intelligence into language education.
PUBLISHED
Keywords: Common European Framework of Reference for Languages (CEFR); Education and minority language; Language Acquisition (first & second); Language Policy; Multilingualism; Second language acquisition; Teaching and learning; Other; Education; Policy